Up close 2 : - Chamot, Anna Uhl (Thomson/Heinle, 2002)
The book is written to meet the needs of today's adult and young adult learners of English. The series' spiraled approach to language learning - presentation, reinforcement, and expansion of communication forms and structures - promotes the gradual but secure development of the listening, speaking, reading, and writing skills required in beginning through intermediate progams.